-1-5n=-7n+3

Simple and best practice solution for -1-5n=-7n+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1-5n=-7n+3 equation:


Simplifying
-1 + -5n = -7n + 3

Reorder the terms:
-1 + -5n = 3 + -7n

Solving
-1 + -5n = 3 + -7n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '7n' to each side of the equation.
-1 + -5n + 7n = 3 + -7n + 7n

Combine like terms: -5n + 7n = 2n
-1 + 2n = 3 + -7n + 7n

Combine like terms: -7n + 7n = 0
-1 + 2n = 3 + 0
-1 + 2n = 3

Add '1' to each side of the equation.
-1 + 1 + 2n = 3 + 1

Combine like terms: -1 + 1 = 0
0 + 2n = 3 + 1
2n = 3 + 1

Combine like terms: 3 + 1 = 4
2n = 4

Divide each side by '2'.
n = 2

Simplifying
n = 2

See similar equations:

| x=2(x^1/2) | | 2.00=(6.00)(8.00)/X | | x=2x^1/2 | | -7x/-1 | | 4.00=(6.00)(8.00)/X | | 5(2x-15)-3x=-124 | | 2x+2(-5x+18)=116 | | x+2-6x=-5.5 | | -14-25= | | 8-4p=1p+13 | | g(t)=-16t^2+100t+7 | | -2cos^2x+cosx=0 | | 3x+2y=7.25 | | 2x+3(2x-12)=36 | | 8y^2x^2=512 | | 2y-x=8x-2 | | 5y^2x^2=125 | | Y=5(-2)-7 | | 2y-3+xy+3x=5 | | 9xy+9xy= | | 3xy-x+9y+2=0 | | 4x^2+8x-4=100 | | log(10)x=0.6 | | -3x^2=-7x+12 | | 3x*y-x+9y+3=13 | | 3.1x-4=2.1x | | (2x^2+1x)+(6x+6)=0 | | ((2x^2)+1x)+(6x+6)=0 | | -3+(-3x)=18 | | 5+.50s=1s | | -5y+1(2)=5 | | -(2-8x)=3(8x-1)-16x+1 |

Equations solver categories